Identificación de las plagas en el cultivo de chocho (Lupinus mutabilis sweet) durante su desarrollo fenológico en la parroquia Eloy Alfaro (chan) cantón Latacunga provincia Cotopaxi - Álvarez Aimacaña, Roberto Carlos (2016)
Research on the theme "Identifying pests in the cultivation of lupine (Lupinus mutabilis Sweet) during their phenological development in the parish Eloy Alfaro (Chan) canton Latacunga Cotopaxi province." It was conducted jointly with the CIAL community group El Chan. It was proposed aimed at identifying pests in the cultivation of lupine (Lupinus mutabilis Sweet) during their phenological development. The specific objectives were: To identify the insect orders during the phenological development of the crop, determine a level of order insects attracted by the different traps according to the phenological state of the crop of lupine, determine the phenological stages of greater presence of pests….